Correction: Gold–carbonyl group interactions in the electrochemistry of anthraquinone thiols self-assembled on Au(111)-surfaces. Issue 21 (9th May 2019) - Wagner, Michal; Qvortrup, Katrine; Grier, Katja E.; Ottosen, Mikkel R.; Petersen, Jonas O.; Tanner, David; Ulstrup, Jens; Zhang, Jingdong
Abstract : Correction for 'Gold–carbonyl group interactions in the electrochemistry of anthraquinone thiols self-assembled on Au(111)-surfaces' by Michal Wagner et al., Chem. Sci., 2019, 10, 3927–3936.